First Global Report of Plasmid-Mediated mcr-1 and Extended-Spectrum Beta-Lactamase-Producing Escherichia coli from Sheep in Portugal - Josman Dantas Palmeira (MDPI AG, 2021)
Resistances to extended-spectrum cephalosporins (ESC) and colistin are One Health issues since genes encoding these resistances can be transmitted between all sectors of the One Health concept, i.e., human, animal, and the environment. Among food-producing animals, sheep farming has long been overlooked. To fill in this knowledge gap, we looked for ESC- and colistin resistance in 21 faecal samples collected from sheep in one farm in the south of Portugal. ESC-resistant isolates were selected on MacConkey agar plates supplemented with cefotaxime. Susceptibility testing was performed by the disk-diffusion method according to CLSI, while colistin MIC was determined by broth microdilution. ESC- and colistin-resistance genes were identified by PCR, and the clonality of all isolates was assessed by XbaI-PFGE. The replicon content was determined by PCR according to the PCR-based replicon typing (PBRT) scheme. Sixty-two non-duplicate ESC-resistant E. coli isolates were identified, which all presented an extended-spectrum beta-lactamase (ESBL) phenotype, mostly due to the presence of CTX-M genes. One CTX-M-1-producing E. coli was concomitantly colistin-resistant and presented the plasmid-mediated mcr-1 gene. Nearly all isolates showed associated resistances to non-beta-lactam antibiotics, which could act as co-selectors, even in the absence of beta-lactam use. The results showed a high proportion of ESBL-producing E. coli in sheep faeces. Their dissemination was very dynamic, with the spread of successful clones between animals, but also a large diversity of clones and plasmids, sometimes residing in the same animal. This study highlights the need for global surveillance in all food-producing sectors, in order to avoid the dissemination of genes conferring resistance to last-resort antibiotics in human medicine.